Geochemical investigations of the success of a dry cover on backfilled pits at Kimheden copper mine, northern Sweden - Villain, Lucile; Alakangas, Lena; Öhlander, Björn (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
Godkänd; 2011; 20111016 (ysko)